SUPLEMENTAÃ‡ÃƒO DE ÃCIDO ASCÃ“RBICO NA ALIMENTAÃ‡ÃƒO DE Bombyx mori L. (LEPIDOPTERA: BOMBYCIDAE) - Miranda, JosÃ© Ednilson; Takashi, Roque; Silva, Alessandra F. da (REVISTA DE AGRICULTURA, 2015)
SUPLEMENTAÃ‡ÃƒO DE ÃCIDO ASCÃ“RBICO NA ALIMENTAÃ‡ÃƒO DE Bombyx mori L. (LEPIDOPTERA: BOMBYCIDAE)